2023
DOI: 10.21203/rs.3.rs-2392726/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UXT-V1 contributes to the malignant phenotypes of colorectal cancer via GSK3β by activating Wnt/β-catenin pathway

Abstract: Background: Colorectal cancer (CRC) is one of malignant tumors that seriously threatening human health. β-catenin is a central hub in Wnt pathway, aberrant activation of Wnt/β-catenin signaling pathway promotes the tumorigenesis/progression of CRC. Methods and Results: Here we found a β-catenin interactor, UXT-V1, could modulate Wnt signaling. The expression of UXT-V1 mRNA was increased in CRC tissues. Overexpression of UXT-V1 increased the canonical Wnt signaling, as evidenced by Wnt reporter systems and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Furthermore, UXT‐V1 upregulated the colonocyte differentiation markers in human IECs, whereas the lack of UXT‐V1 led to the downregulation of MUC2 and VIL1, the differentiation markers for enterocytic lineages. Contradictory to our findings, a recent study showed that UXT‐V1 expression in CRC tissues is higher than that in the corresponding para‐cancerous tissues and promotes CRC cell growth 21 . Thus, the exact function of UXT‐V1 may depend on the cell type.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Furthermore, UXT‐V1 upregulated the colonocyte differentiation markers in human IECs, whereas the lack of UXT‐V1 led to the downregulation of MUC2 and VIL1, the differentiation markers for enterocytic lineages. Contradictory to our findings, a recent study showed that UXT‐V1 expression in CRC tissues is higher than that in the corresponding para‐cancerous tissues and promotes CRC cell growth 21 . Thus, the exact function of UXT‐V1 may depend on the cell type.…”
Section: Discussionsupporting
confidence: 69%
“…Contradictory to our findings, a recent study showed that UXT-V1 expression in CRC tissues is higher than that in the corresponding para-cancerous tissues and promotes CRC cell growth. 21 Thus, the exact function of UXT-V1 may depend on the cell type. .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations